Markov Random Field Based Model In Spatial Domain for Denoising of Microarray Images - Nandihal, Priya; Bhat, Vandana S; Pujari, Jagadeesh D (International Journal of Computer Sciences and Engineering, 2018)
Bioinformatics research is an active area of research that employs DNA microarray technology as a very important tool. Microarray gene expression is acquired through microarray technology in order to monitor the expression of genes under different conditions. Denoising is a major pre-processing step in DNA microarray images. This paper proposes a new spatial denoising technique in spatial domain for DNA microarray image. The method exploits Markov Random Field (MRF) model to reduce the noise in microarray images. Two algorithms developed in this work are Denoising using MRF (DMRF) and Determination of Optimized Values (DOV).Different experimental results and analysis demonstrate the performance of the proposed method with existing methods using various performance metrics.